Aspiration pneumonia in nursing literature—a mapping review - Lisiecka, Dominika; Kearns, Áine; Evans, William; Farrell, Dawn (Frontiers in Rehabilitation Sciences, 2024)
IntroductionAspiration pneumonia (AP) is an infection of the lungs caused by inhalation of material. The reported incidences vary across literature and clinical populations and is associated with high morbidity and mortality. Management of AP is best carried out by a multidisciplinary team.MethodsThis aim of this review was to collate and describe the available evidence on AP to develop a greater understanding of the concept of AP as it is represented in the nursing literature. As a collaborative team, we undertook the six stages of a systematic mapping review. We searched for the term aspiration pneumonia in 200 peer reviewed nursing journals across 10 databases, over a ten-year period (2013–2023).ResultsIn this review, 293 papers were coded. Dysphagia, oral health and tube feeding emerged as the most frequent risk factors for AP, and the most reported factors for preventing this condition. Mortality was the most commonly described consequence of AP, followed by hospitalisations and morbidity. Multiple management approaches were reported including dysphagia assessment, risk evaluation, oral care and texture modification of food and fluids. The role of nurses and interprofessional collaborations were described.DiscussionDespite limited evidence related to the topic of AP in the nursing literature, the complexity of the causes, prevention, management and consequences of AP emerged. Certain factors, such as dysphagia, oral health, and tube feeding, were described under prevention, cause and management of AP. The importance of multidisciplinary approach in the management and prevention of AP was presented.